THE WORKLOAD ANALYSIS OF EMPLOYEE BY USING NATIONAL AERONAUTICS AND SPACE ADMINISTRATION-TASK LOAD INDEX METHOD (NASA-TLX) - Nur Azemil (Jenderal Soedirman University, 2017)
Development of manufacturing and service institutions can not be separated from the role of human resources. Human resources have an important role in fulfilling vision and mission. University of A is one of the private educational institutions in East Java to achieve the goal must be managed properly that can be utilized optimally, this can be done by analyzing workload and performance or optimizing the number of employees. The purpose this research is measure workload and effect the employee’s performance. Measurement of workload is using National Aeronautics and Space Administration-Task Load Index (NASA-TLX) method, NASA-TLX method is rating multidimentional subjective mental workload that divides the workload based on the average load of 6 dimensions, and the measurement of performance is using questionnaire with 5 scales by likert scale. The results showed that employees who have Medium workload is 8%, High workload is 84% and Very high workload is 8%. The result of the questionnaire showed the category of employee’s performance, simply performance is 24% and satisfactory performance is 76%. From the statistical test by using Chi Square method, it is known that the value = 5,9915 and = 2,2225, the result shows < , then is accepted and is rejected. Thus, there is influence between the workload of employees and the employees’s performance.